JURISDIÇÃO NO DIREITO AMBIENTAL: ANÁLISE DA COMPETÊNCIA CÍVEL EM DESASTRES AMBIENTAIS - Nogueira, Elton Pupo; Silva, Marina Alvarenga Medeiros da (Revista da AJURIS - Qualis A2, 2023)
JURISDICTION IN ENVIRONMENTAL LAW: ANALYSIS OF CIVIL ACTION IN ENVIRONMENTAL DISASTERS ÁREA(S): direito ambiental; direito constitucional. RESUMO: O presente estudo analisou a competência nas demandas coletivas, regida especialmente pela Lei das Ações Civis Públicas (LACP) e pelo Código do Consumidor (CDC). Neste contexto, especialmente na perspectiva do Direito Ambiental, foram analisados o caso Brumadinho/MG e as decisões proferidas por tribunais sobre tema. Buscou-se, a partir das conceituações doutrinárias e jurisprudenciais, especialmente no que toca o dano local, regional e nacional, uma melhor compreensão da competência em demandas que envolvem interesses difusos, coletivos e individuais homogêneos para maior eficiência na condução desses casos. ABSTRACT: The present study analyzed the rules on jurisdictional competence in class actions, which is governed especially by the Law on Public Civil Actions (LACP) and the Consumer Code (CDC). In this context, especially considering the Environmental Law perspective, the Brumadinho case has been analysed from both doctrinal and jurisprudential concepts about local, regional and national damages. Based on the study hose situations, conclusions and normative interpretations were demonstrated to provide greater efficiency in handling those cases. With the aim of better understanding the jurisdictional competence rules in collective actions and ensure an efficient handling and outcome, this study has analysed the interpretation of doctrine and jurisprudence concepts, especially with regards to local, regional and National damages. PALAVRAS-CHAVE: competência; danos difusos e coletivos; Brumadinho. KEYWORDS: competence; diffuse and collective damages; Brumadinho. SUMÁRIO: Introdução; 1 Desenvolvimento; Considerações finais; Referências. SUMMARY: Introduction; 1 Development; Final considerations; References.